If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 * 5 + 8y = 3 Multiply 2 * 5 10 + 8y = 3 Solving 10 + 8y = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 8y = 3 + -10 Combine like terms: 10 + -10 = 0 0 + 8y = 3 + -10 8y = 3 + -10 Combine like terms: 3 + -10 = -7 8y = -7 Divide each side by '8'. y = -0.875 Simplifying y = -0.875
| 20x^2+11x-7=-4 | | 2x/(x-3)=4-(6/(x-3)) | | x^2-4.5x=0 | | x+25=34 | | (180-x)-3(90-x)=20 | | n+46=76 | | 1/(x+1)+3=7/(x+1) | | 6(x+6)=9+5x | | 6/12x+8/12=9/12 | | n+46=72 | | 89x-3x=2x+14 | | -9x-5=-23 | | 5z-8=-5+6z | | (180-x)-3(90-x)=30 | | a+7/3=4 | | 5x+3*0=12 | | X^2-3x+16= | | x^2+3xy-5x-3y+y^2=0 | | 8x+9=9x-2x | | -5*(3^2-2)+(7*5+7)/6 | | -x+1.9=0.4+2x | | y=cx-dx | | x-0.8=8.39 | | 6=8x+10 | | 35+8x= | | 32t=-160 | | (x+8)/10=8/5+(x-2)/3 | | r-4r-3s+10s-3t+8t=0 | | 4-1/3a=10 | | 6(m-6)+4(3m+4)=17(m-2)-2 | | 26+4y-10=13y-12-2y | | -13=k-16 |